THE EFFECT OF UNDERSTANDING THE ACCOUNTANT’S CODE OF ETHICS AND STUDENT SPRITUAL INTELLIGENCE ON THE ETHICAL BEHAVIOR OF ACCOUNTING STUDENT - Elizabeth Febrica Ambarita; Martinus Budiantara (Jurnal Scientia, 2023)
This study aims to examine the effect of understanding the code of professional ethics of accountants and students' spiritual intelligence on the ethical behavior of accounting students at Mercu Buana University, Yogyakarta. This study uses the variables Understanding of the Accountant Professional Code of Ethics and Student Spiritual Intelligence as independent variables and Student Ethical Behavior as the dependent variable. In this study the data used were primary data collected through a questionnaire survey at Mercu Buana University, Yogyakarta in 2023. The sampling method used in this study was the purposive sampling method. The sample in this study were 110 students who met the criteria as respondents in this study. The analysis in this study uses multiple linear regression using SPSS software. The results of this study indicate that the understanding of the Code of Ethics for the Accountant Profession and the Spiritual Intelligence of Students has an important role in shaping the ethical behavior of accounting students at Mercu Buana University, Yogyakarta.